New insights into cerium anomalies and mechanisms of trace metal enrichment in authigenic carbonate from hydrocarbon seeps - Hu, Y; Feng, D; Peckmann, J; Roberts, H H; Chen, D (Chemical Geology, 2014)
Authigenic carbonates that form at marine hydrocarbon seeps provide a unique geological archive of past local environmental conditions and pore fluid geochemistry. Recent work on such carbonates revealed variable cerium (Ce) anomalies and anomalous enrichments of certain trace metals. However, the mechanisms accounting for such anomalies remain poorly constrained. Here, we characterize the rare earth element (REE) patterns of carbonate phases and the trace metal patterns of bulk carbonate rocks sampled at three hydrocarbon seeps located at Congo Fan pockmarks (CF) and the Gulf of Mexico sites AC645 and GB425. The analyzed CF, GB425, and AC645 carbonates yielded different REE patterns, displaying positive, no, as well as negative Ce anomalies. The covariation of molybdenum (Mo) with uranium (U), including authigenic Mo (Moauth) and U (Uauth) enrichments as well as (Mo/U)auth ratios proved useful to obtain new insight into the applicability of Ce anomalies to constrain past redox conditions. Trace element patterns suggest that (1) CF carbonates formed in a restricted sulfidic environment, while (2) the AC645 site experienced intermittent oxygenation causing negative Ce anomalies, and (3) environmental conditions were variable at the GB425 mud volcano site. Interestingly, GB425 carbonates show significant Mo, arsenic (As), and antimony (Sb) enrichments with the enrichment factor of As (AsEF) correlating well with the authigenic Fe fraction. These results suggest that iron oxyhydroxides played an important role in the adsorption of Mo, As, and Sb in the water column and their transfer to the sediment. The combination of trace metal and REE geochemistry of authigenic carbonates used here is a promising tool to better assess past variability of redox conditions and biogeochemical processes at marine hydrocarbon seeps.
Keywords: HOV Alvin (Human Occupied Vehicle)